Women in monitoring positions and market risk. Are the stocks of companies with gender diverse boards less volatile? - Valls Martínez, María del Carmen; Soriano Román, Rafael (Frontiers in Psychology, 2022)
Gender equality is included in the United Nations Sustainable Development Goals and in the Global Jobs Pact of the International Labour Organization. Many countries, especially in Europe, are incorporating legal quotas into their legislation to oblige companies to increase the presence of women in the highest positions of responsibility. This measure has been controversial and widely debated, and so it is of great interest to analyze the economic effects that the incorporation of women brings. The aim of this paper is to analyze the relationship between the percentage of women on the board of directors and systematic market risk, measured using the beta of stocks in the S&P 500 and Euro Stoxx 300 indexes from 2015-2019. Applying OLS regressions with instrumental variables, fixed effects panel data, and a GMM estimation, the results show a negative and significant relationship for the U.S. market. However, this relationship was not confirmed for the European market.